PELATIHAN ECO-ENZYM MELALUI PENDEKATAN SOSIAL EKONOMI PADA IBU-IBU PKK DESA JOGOROGO UNTUK MEWUJUDKAN KEMANDIRIAN EKONOMI - Erlinda Harum Ramandha; Nuzula Asmawati; Zulfa Istiqomah; Aliffya Nori Nur Qolbu Jannah; Umi Ma’arifah; Dwi Nila Andriani (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract The implementation of this Community Service PKM activity aims to provide eco-enzyme training to partners aimed at PKK mothers in the Jogorogo Village environment, Jogorogo District, Ngawi Regency to process their kitchen waste into useful liquids for the earth. This dedication aims to solve the problem of stacking kitchen waste that mounts to be processed into eco-enzyme liquid. The steps taken in achieving the objectives of PKM-PM begin with observation of environmental conditions, socialization about eco-enzymes, eco-enzyme training, monitoring the development of eco-enzymes, and ending with eco-enzyme harvesting activities. PKM activities will be published in journals, articles, and social media, so that it can be known by the wider community, that there is training on making eco-enzymes given to PKK mothers in Jogorogo Village in an effort to realize economic independence and utilize kitchen waste. Keywords: Eco-enzyme training, socio-economic, Economic Independence